Association between intraoperative tidal volume and postoperative acute kidney injury in non-cardiac surgical patients using a propensity score-weighted analysis - Ji-Yoon Jung; Seung Eun Song; Suhyun Hwangbo; So Yeong Hwang; Won Ho Kim; Hyun-Kyu Yoon (Scientific Reports, 2024)
Abstract Acute kidney injury (AKI) is related to adverse clinical outcomes. Therefore, identifying patients at increased risk of postoperative AKI and proactively providing appropriate care is crucial. However, only a limited number of modifiable risk factors have been recognized to mitigate AKI risk. We retrospectively analyzed adult patients who underwent endotracheal intubation and mechanical ventilation of more than 2 h during non-cardiac surgery at Seoul National University Hospital from January 2011 to November 2022. Patients were grouped into low- or high-tidal volume groups based on their intraoperative tidal volume relative to their predicted body weight (PBW) of 8 ml/kg. The association between intraoperative tidal volume and postoperative AKI was evaluated using inverse probability of treatment weighting (IPTW), adjusting for various preoperative confounders. Among the 37,726 patients included, the incidence of postoperative AKI was 4.1%. The odds of postoperative AKI risk were significantly higher in the high-tidal volume group than in the low-tidal volume group before and after IPTW (odds ratio [OR] 1.20, 95% confidence interval [CI] 1.08–1.32, P = 0.001 and OR: 1.10, 95% CI 1.02–1.19, P = 0.010, respectively). In the multivariable logistic regression analysis after IPTW, a high tidal volume was independently associated with an increased risk of postoperative AKI (OR: 1.21, 95% CI 1.12–1.30, P < 0.001). In this propensity score-weighted analysis, an intraoperative high tidal volume of more than 8 ml/kg PBW was significantly associated with an increased risk of postoperative AKI after IPTW in non-cardiac surgical patients. Intraoperative tidal volume showed potential as a modifiable risk factor for preventing postoperative AKI.